2013
DOI: 10.1186/1471-2369-14-170
|View full text |Cite
|
Sign up to set email alerts
|

Low agreement between cardiologists diagnosing left ventricular hypertrophy in children with end-stage renal disease

Abstract: BackgroundMonitoring of the appearance of left ventricular hypertrophy (LVH) by echocardiography is currently recommended for in the management of children with End-stage renal disease (ESRD). In order to investigate the validity of this method in ESRD children, we assessed the intra- and inter-observer reproducibility of the diagnosis LVH.MethodsEchocardiographic measurements in 92 children (0–18 years) with ESRD, made by original analysists, were reassessed offline, twice, by 3 independent observers. Smalles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The diagnostic methodology could be one potential factor explaining the discrepancy in our findings. Indeed, Schoenmaker et al [ 41 ] show high variations in LVMI analyses between observers, while TDI has been shown to be a sensitive method to assess cardiac dysfunction [ 30 ]. Further, we acknowledge small differences in results where analyses are based on FGF23 z -score or its raw unadjusted data, which could be another reason for differences between studies.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic methodology could be one potential factor explaining the discrepancy in our findings. Indeed, Schoenmaker et al [ 41 ] show high variations in LVMI analyses between observers, while TDI has been shown to be a sensitive method to assess cardiac dysfunction [ 30 ]. Further, we acknowledge small differences in results where analyses are based on FGF23 z -score or its raw unadjusted data, which could be another reason for differences between studies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, LV mass increased in 21 % of the dialysis patients and 24 % of the renal transplant patients, suggesting some degree of LVH, but the presence of LVH did not seem to be a risk factor for the decrease in LS, in turn suggesting that the changes in strain can be present in ESRD patients in the absence of LVH. However, it should be noted that the measurement of LVH in pediatric ESRD has already been shown to be less reliable, as demonstrated by Schoenmaker et al [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, reports on the reproducibility and validity of this assessment in children are scarce. In an earlier study of the same cohort, we found conventional echocardiography to be insufficiently sensitive and accurate for a reliable diagnosis of left ventricular hypertrophy 4 . Tissue Doppler imaging appears to be a promising method for the detection and quantification of subtle abnormalities in diastolic ventricle function in adults 5 .…”
mentioning
confidence: 86%
“…In an earlier study of the same cohort, we found conventional echocardiography to be insufficiently sensitive and accurate for a reliable diagnosis of left ventricular hypertrophy. 4 Tissue Doppler imaging appears to be a promising method for the detection and quantification of subtle abnormalities in diastolic ventricle function in adults. 5 In order to investigate whether this method would also be useful in children with end-stage renal disease, we compared the accuracy of two echocardiographic techniques, that is, conventional echocardiography and tissue Doppler imaging, to detect impairment of left ventricular diastolic function.…”
mentioning
confidence: 99%